Anglo-Sakson Protestan teşkilatlarının Türkiye’deki faaliyetleri (1950-2000) - Haboubi, Ferida (My University, 2010)
Bu çalışmada Osmanlı döneminde yöğun alarak faaliyette bulınan Anglo-Sakson (Amerika ve Britanya) Protestan misyonerlik faaliyetleri, Türkiye Cumhuriyeti’nde devam ettirmişledi. Protestanlık, 16 yüzyılda Martin Luther öncülüğünde Katolok kilisesi’ne ve Papa’nın otoritesine karşı girişilen reform hareketi’nin sonucu Protestan mezhebi doğmuş ve kendi içinde çeşitli kiliseler ve gruplar ortaya çıkmıştır. Bu Hıristiyan grupları Protestanlaştırma amacıyla kendi ülkelerinde cemiyetler ve kuruluşlar açtılar. Daha sonra, 19.yüzyılın başlangçta Anglosakson misyonerler Osmanlı Devleti’nde yoğun misyon faaliyeti içerisine girmişlerdir.Özellikle Tanzımat Fermanı ve İslahat Fermanı benimsemiyle Anglosakson misyonerler Osmanlı topraklarında çeşitli seviyerlerde eğitim, sağlık ve basın-yayın müesseseleri yönelik vasıtasıyla çalışmaları gerkçekleşiyorlardı. Osmanlı Ülkesinde faaliyet gösteren Amerikan Protestan misyon örgütlerinden en kadımlı ve büğünü ABCFM ve Amerikan Bible Society’dir. Britanya misyoner ise yoğunlaşan faaliyetler Church Missionary Society ve British and Foreign Bible Society’dir. Atatürk dönemi ve Türkiye Cumhuriyeti’nin kurulusuyla birlikte milli eğitim politikasının ve laiklık esasları benimseyen, misyoner okulları çoğu kapanmış ve din propaganda yasaklanmış, Ayrıca, misyoner okulları ve hastanelerinde üzerinde ağır vergiler konmuştur ve bazı misyoner müesseseler Türkiye Hükümetince ele konulmuştur. Dolaysıyla, Anglosakson Protestan faaliyetleri azaltmalara neden olmuştur. 1961’den sonra misyoner faaliyetleri yine canlanmıştır.Bazı eğitim ve sağlık kurumları Sağlık ve Eğitim Vakfı tarafından yeniden açıldı. Misyonerlik örgütleri farklı metodlar ücretsiz

kursu, öğrenci kampları, radyo, internet ve dernekler gibi vasıtasıyla Türkiye’de misyoner faaliyetleri yoğunlamıştır, hatta bazı Türkler Hıristiyanlaştıkları görülmektedir. ABSTRACT The purpose of this research paper is to articulate a consise history of the Anglo-Saxon Protestan mission activities in Turkey throughout a progessive period of time. Early in the 17th. Century United States of America and Great Britain established institutions in the home country espacially naming, The Church Missionary Society, The British and Foreign Bible Society, The American Bible Society and The American Bible Commissioners for Foreign Missions (ABCFM). At the beginning of the 19th.century these Anglosakson organizations strated to enlarge the scope of its activities, then it developed commercial and diplomatic institutions in the Ottoman Empire in order to reach its aim. With the Declaration of the political reforms of 1839 and 1856 in the Constantinople State, mission activities gained more rights and religious freedom. As aresult, missionary schools, hospitals, publishing facilities, orphanage and other institutions covered the whole Empire. The largest Anglosakson mission in the Empire was ABCFM, it occupied principal stations and other out-stations. A misson in İstanbul was established as a center for all its missionary work. With the collapse of the Ottoman Empire, the Anglosakson missionaries were not easier than before. Mustafa Kemal who proclaimed the Turkish Republic in 1923, issued a series of educational, social and political reforms. The secular state and the principles of Atatürk were opposed to missionary activities. Especially, a number of taxes were imposed on mission work in the land in question. As a result, many shools, hospitals and other institutions were closed. İn 1960 and especially in 1980 with the introduction of new missionary methods, the Anglosakson Protestan missionary work took another dimension and a new phase. The publishing and distributing of religious books and pamphlets for free in the streets, free English courses, free computer courses, financial aids, student camps, subvention for Türk students to study abroad and other facilities were introduced as a strategy to convert the community with wich they came in contact to Christianity and thus Protestantism.
Keywords: Protestanlık; Türkiye_Protestanlık